Some writer! : the story of E.B. White - Sweet, Melissa (Boston : Houghton Mifflin Harcourt, 2016)
"SOME PIG," Charlotte the spider's praise for Wilbur, is just one fondly remembered snippet from E.B. White's Charlotte's Web. In this book, Melissa Sweet mixes White's personal letters, photos, and family ephemera with her own artwork to tell his story, from his birth in 1899 to his death in 1985.
All's right with the world department -- Once more to the lake -- Years of wonder -- From sea to shining sea -- Answers to hard questions -- A time of enchantment -- Stuart Little -- Bad news -- Charlotte's Web -- The Elements of Style -- The trumpet of the Swan -- What do our hearts treasure? -- Sentences we hated to come to the end of.
Includes bibliographical references (pages 152-156) and index.
Reading Counts!
Keywords: White, E. B. -- 1899-1985 -- Juvenile literature; Authors, American -- 20th century -- Biography -- Juvenile literature; Children's stories -- Authorship -- Juvenile literature; White, E. B. -- 1899-1985.; White, E. B. -- 1899-1985.; Authors; Authorship; Children's stories -- Authorship -- Juvenile literature; Authors, American -- 20th century -- Biography -- Juvenile literature; Authorship; Illustrated children's books; Biographies